HUMANIST RELIGIOUS VALUES BASED ISLAMIC EDUCATION CURRICULUM: AN ANALYSIS OF PHILOSOPHICAL FOUNDATIONS AND GLOBAL NEEDS - Fajar Sidik; Muhamad Azim; Marlina Marlina (Jurnal Ikhtibar Nusantara, 2026)
The urgency to reform the Islamic Religious Education (PAI) curriculum stems from a widening gap between its normative-dogmatic orientation and the global demand for inclusive, humanistic education. Although Islamic teachings emphasize compassion, justice, and respect for human dignity, these values are not yet systematically embedded in current curriculum structures. Previous studies have examined humanistic-religious education in limited scopes, but few have explored its philosophical foundations and global relevance. This study investigates how humanistic-religious values can be philosophically integrated into the PAI curriculum to meet global educational needs. Employing a qualitative method with a normative-philosophical approach, data were gathered through literature review and document analysis of curriculum texts and scholarly works. The data were analyzed using thematic reduction, categorization, and synthesis. The study offers a significant contribution by proposing a curriculum framework that balances spiritual and social dimensions, rooted in Islamic ethics and responsive to multicultural realities. It recommends a conceptual shift in curriculum design, teacher training in transformative pedagogy, and policy support for embedding universal human values into religious education. These findings enrich the discourse on global Islamic education and provide a foundation for future empirical research and curriculum innovation.